KEBIJAKAN PEMBERIAN IZIN USAHA TOKO MODERN ALFAMART DAN INDOMARET OLEH PEMERINTAH KOTA PEKANBARU BERDASARKAN PERATURAN PRESIDEN NOMOR 112 TAHUN 2007 TENTANG PENATAAN DAN PEMBINAAN PASAR TRADISIONAL, PUSAT PERBELANJAAN DAN TOKO MODERN - Jun Ramadhani; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The phenomenon of the existence of modern stores Alfamart and Indomaret in some corner of the city of Pekanbaru drawn some criticism and criticism from all walks of life. In the middle of the street vendors curbing the negative spotlight of the City of Pekanbaru, modern shop license Alfamart and Indomaret actually get preferential treatment. The existence Alfamart and Indomaret accused some parties do not make an impact on the feasibility study of social advance, ranging from the number of stores spread, until the operating hours using a 24 -hour system. Pekanbaru City Government should make an assessment before the permit is issued. This study was published that zoning Alfamart and Indomaret not interfere with traditional merchant . Evaluation of this policy can be seen also that social policies are given by the government in the development of modern store is not applied by the investors. This type of research is classified into types of socio-juridical research , because they directly study conducted research on the location or place under study in order to give a complete picture of the problem under study. Location of research conducted in the Office of Integrated Service Agency Pekanbaru, Office of Industry and Commerce Pekanbaru, and Outlet Stores modern Alfamart and Indomaret Pekanbaru City and Personal Kiosk. While the population and the sample is the whole party soon is related to the problem under study and this study, the data sources used, the primary data, secondary data and data tertiary, techniques of data collection in this study with the observation, interview, and literature study.Keywords : Juridical Analysis – Decision Constitutional Court - KUHAP